Demam Korea: Minat Beli Terhadap Produk Kecantikan Korea (K-Beauty) - Jenia Hanindita Rahmawati; Muhamad Ahsan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research aims to examine the effect of brand image, celebrity endorser, country of origin and electronic word of mouth on buying interest in Korean beauty products (K-Beauty). The method used is quantitative associative. The sampling technique used is accidental sampling as many as 108 respondents. Data was collected by distributing online questionnaires via a google form. The collected data was analyzed using Structural Equation Modeling (SEM) which consists of two stages, namely the measurement model and the structural model with IBM SPSS AMOS software version 20 and index number analysis as descriptive analysis. The results showed that brand image has a positive and significant effect on buying interest in Korean beauty products (K-Beauty). While celebrity endorsers, country of origin and electronic word of mouth have no effect on buying interest in Korean beauty products (K-Beauty).